Effect of Plant Extracts on Seed Borne Fungi of Vigna radiata - Kolhe2, Vasant P. Pawar1*; A. S. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">Present paper deals with the study of antifungal properties of botanicals like leaf extracts, rhizome and seed extracts of different plants. Ten % aqueous leaf extract of Parthenium hystrophorus; Azadirachta indica; Adhatoda Vasica and Aegle marmelos retarded the growth of Alternaria alternata, Aspergillus flavus, Curvularia lunata, Fusarium roseum and Trichoderma viride. Rhizome and seed extracts of all tested plants retarded the growth of Alternaria alternata, Aspergillus flavus, Curvularia lunata, Fusarium roseum and Trichoderma viride at 10 % while rhizome extract of Musa paradisiaca stimulated the growth of Trichoderma Viride. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">— 1Department of Botany, Arts & Science College, Bhalod, Tq. Yawal Dist. Jalgaon, (M.S.), IndiaÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â 2Department of Zoology, Arts & Science College, Bhalod, Tq. Yawal Dist. Jalgaon, (M.S.), IndiaÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â — Please Cite This Article As: Vasant P. Pawar and A. S. Kolhe. 2010. Effect of Plant Extracts on Seed Borne Fungi of Vigna radiata J. Ecobiotechnol. 2(6):44-45. Â